Bats of Guilan, northern Iran: a review and uncovering novel discoveries, with comments on two key cave roosts - Zahra Malekpourfard; Vahid Akmali (Iranian Journal of Animal Biosystematics, 2023)
Guilan province, located in northern Iran and surrounded by the Caspian Sea to the north and the Hyrcanian forests to the south, boasts the most diverse habitats in the country. However, there is a lack of information on bat fauna in the caves of Guilan province, with all existing records limited to artificial roosts, foraging individuals or echolocation calls. Despite this, available data suggests that 13 species of bats have been reported in the region. In this study, 12 caves throughout the province were observed, resulting in the identification of five bat species, namely Miniopterus pallidus, Pipistrellus pipistrellus, Myotis blythii, Rhinolophus hipposideros, and R. ferrumequinum. One colony and two individuals in separate localities were also identified at the generic level as Rhinolophus sp., while two cave roosts with large populations and considerable number of species were described in detail. Furthermore, this study encompasses data on five new sample records, comprising three from Pipistrellus kuhlii, one from Rhinolophus sp., and one from Rhinolophus hipposideros, from foraging individuals and artificial roosts. Overall, these findings contribute to our understanding of the diversity and distribution of bats in Guilan province, particularly within its caves.